2017
DOI: 10.1371/journal.pone.0173864
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory study the effects of oxygen-containing functional groups on oxygen molecules and oxygen atoms adsorbed on carbonaceous materials

Abstract: Density functional theory was used to study the effects of different types of oxygen-containing functional groups on the adsorption of oxygen molecules and single active oxygen atoms on carbonaceous materials. During gasification or combustion reactions of carbonaceous materials, oxygen-containing functional groups such as hydroxyl(-OH), carbonyl(-CO), quinone(-O), and carboxyl(-COOH) are often present on the edge of graphite and can affect graphite’s chemical properties. When oxygen-containing functional grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Such -OH and ]O moieties being surface-or edge-bound are expected to lead to the spin redistribution and charge delocalization on the neighbouring metal atoms, 34 affording active centers. 35…”
Section: Resultsmentioning
confidence: 99%
“…Such -OH and ]O moieties being surface-or edge-bound are expected to lead to the spin redistribution and charge delocalization on the neighbouring metal atoms, 34 affording active centers. 35…”
Section: Resultsmentioning
confidence: 99%
“…As a result, electron transfer requires oxygen molecules to interact directly with the carbon surface through physisorption or chemisorption. Density functional theory (DFT) models have shown that the energy required for adsorption of oxygen molecules to graphitic surfaces near carboxyl moieties is nearly twice that of the same process near carbonyl moieties [57] . This indicates that the presence of carboxyl functionalities makes the physisorption of oxygen molecules less likely, while the physisorptive interactions of oxygen molecules with graphitic surfaces containing carbonyl are more stable [57] .…”
Section: Resultsmentioning
confidence: 99%
“…Density functional theory (DFT) models have shown that the energy required for adsorption of oxygen molecules to graphitic surfaces near carboxyl moieties is nearly twice that of the same process near carbonyl moieties [57] . This indicates that the presence of carboxyl functionalities makes the physisorption of oxygen molecules less likely, while the physisorptive interactions of oxygen molecules with graphitic surfaces containing carbonyl are more stable [57] . Other DFT models have found that the carboxyl group itself interacts only weakly with O 2 molecules, while the interaction between pristine and defective CNT surfaces can lead to physisorption and chemisorption, respectively [58] .…”
Section: Resultsmentioning
confidence: 99%
“…A recent work reported that graphite layers can present oxidized groups in some extension, such as hydroxyl, carbonyl, and carboxyl . The existence of such hydrophilic spots along the structure could favor the charging of the electric double layer, and then increase the associated capacitive current.…”
Section: Resultsmentioning
confidence: 99%
“…[28,29] A recent work reported that graphite layers can present oxidized groups in some extension, such as hydroxyl, carbonyl, and carboxyl. [30] The existence of such hydrophilic spots along the structure could favor the charging of the electric double layer, and then increase the associated capacitive current. Considering that most of the hydroxyl groups present in the starch structure are involved in hydrogen bonds between different chains that present little interaction with the external environment, [31] we believe that the incorporation of the studied starch samples in the carbon paste could attenuate the effect of the hydrophilic groups from the graphite structure, which would result in a lower background current.…”
Section: Electrochemical Study Of the Starch Modified Carbon Paste Elmentioning
confidence: 99%